2017
DOI: 10.1021/acschembio.7b00053
|View full text |Cite
|
Sign up to set email alerts
|

The Macrolide Toxin Mycolactone Promotes Bim-Dependent Apoptosis in Buruli Ulcer through Inhibition of mTOR

Abstract: Mycolactone, the macrolide exotoxin produced by Mycobacterium ulcerans, is central to the pathogenesis of the chronic necrotizing skin disease Buruli ulcer (BU). Here we show that mycolactone acts as an inhibitor of the mechanistic Target of Rapamycin (mTOR) signaling pathway by interfering with the assembly of the two distinct mTOR protein complexes mTORC1 and mTORC2, which regulate different cellular processes. Inhibition of the assembly of the rictor containing mTORC2 complex by mycolactone prevents phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 45 publications
4
78
0
Order By: Relevance
“…Short‐term (4–16 h) exposure to mycolactone induced rapid alterations in the actin cytoskeleton of HeLa cells, coinciding with a defective capacity of the cells to establish adhesive contacts and migrate directionally in wound‐healing assays in vitro [Guenin‐Mace et al., ]. In all skin cells studied, longer treatments (>48 h) induced cell retraction followed by detachment and apoptosis, albeit with slight differences in time‐to‐death across cell types [Bieri et al., ; Dangy et al., ; Gama et al., ; George et al., ; Guenin‐Mace et al., ; Ogbechi et al., ; Snyder and Small, ]. In human dermal microvascular endothelial cells, mycolactone treatment also resulted in the depletion of the blood coagulation regulator thrombomodulin from the cell surface [Ogbechi et al., ].…”
Section: Buruli Ulcer the Third Most Common Mycobacterial Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Short‐term (4–16 h) exposure to mycolactone induced rapid alterations in the actin cytoskeleton of HeLa cells, coinciding with a defective capacity of the cells to establish adhesive contacts and migrate directionally in wound‐healing assays in vitro [Guenin‐Mace et al., ]. In all skin cells studied, longer treatments (>48 h) induced cell retraction followed by detachment and apoptosis, albeit with slight differences in time‐to‐death across cell types [Bieri et al., ; Dangy et al., ; Gama et al., ; George et al., ; Guenin‐Mace et al., ; Ogbechi et al., ; Snyder and Small, ]. In human dermal microvascular endothelial cells, mycolactone treatment also resulted in the depletion of the blood coagulation regulator thrombomodulin from the cell surface [Ogbechi et al., ].…”
Section: Buruli Ulcer the Third Most Common Mycobacterial Diseasementioning
confidence: 99%
“…Importantly, both studies conclude that a sustained, mycolactone‐mediated, Sec61 blockade triggers cellular stress responses that eventually induce apoptosis via the ATF4/C/EBP homologous protein/Bim signalling pathway [Morel et al., ; Ogbechi et al., ]. The ability of mycolactone to induce apoptosis via Bim may be further enhanced as a consequence of its inhibition of the mammalian target of rapamycin signalling pathway [Bieri et al., ].…”
Section: Mycolactone‐mediated Sec61 Blockade and Clinical Manifestatimentioning
confidence: 99%
“…It appears that adaptive immune responses associated with IFN‐γ secretion may be crucial. The cytopathic effect of the macrolide toxin causes apoptosis of mammalian cells and down‐regulates local and systemic immune responses by interfering with the activation of immune cells, which may account for poor inflammatory responses in BU lesions (Fig. ).…”
Section: Immune Suppression Associated With Bu Diseasementioning
confidence: 99%
“…subsequently reported that BU patients with active ulcers showed distinctive profile of immune suppression marked by down modulation of selected cytokines and an impaired capacity to produce Th1, Th2, and Th17 cytokines when stimulated with mitogenic agents . Immunohistopathological studies of lesions from BU patients after SR regimen have demonstrated treatment‐associated initiation of vigorous immune responses and the development of ectopic lymphoid tissue in the BU lesions . Three different general types of infiltration, diffuse mixed infiltrates, granulomas, and dense lymphocyte aggregation, near vessels were observed.…”
Section: Immune Suppression Associated With Bu Diseasementioning
confidence: 99%
“…Mycolactone increases expression of the pro-apoptotic regulator Bim in mammalian cells, driving them into apoptosis (Bieri et al, 2017). At low concentrations, mycolactone counteracts many functions of tissue-resident macrophages and monocytes by inhibiting the production of several cytokines and chemokines including TNF and IFNG (Simmonds et al, 2009; Torrado et al, 2010; Fraga et al, 2011).…”
Section: Introductionmentioning
confidence: 99%